2013
DOI: 10.1021/ef400142v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight and Density Distributions of Asphaltenes from Crude Oils

Abstract: Asphaltenes self-associate, and the molecular weight and density distributions are a factor in asphaltene precipitiation. To determine these distributions, heptane-extracted asphaltenes from four crude oils were fractionated into solubility cuts. The asphaltenes were dissolved in toluene and then partially precipitated at specified ratios of heptane/toluene to generate sets of light (soluble) and heavy (insoluble) cuts. The molecular weight and density were measured for each cut. The asphaltenes were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…Both mechanisms reproduce the correct effect of aging on the initial adsorption rate and adsorbed mass 41 prior to rinsing, Figs. 8 and 10.…”
Section: Surface Recombinationmentioning
confidence: 63%
See 3 more Smart Citations
“…Both mechanisms reproduce the correct effect of aging on the initial adsorption rate and adsorbed mass 41 prior to rinsing, Figs. 8 and 10.…”
Section: Surface Recombinationmentioning
confidence: 63%
“…Rudrake and Rudrake et al reasoned from QCM and XPS data 25 that, given an apparent film thickness of 6-8 nm, the likely arrangement was edge-on or 'vertical' [40,20]. 26 Based on reported literature values [41,42,43,44,45], we adopt an asphaltene density of 1.2 gcm⁻³ and 27 estimate that the thickness of the adsorbed asphaltene film in our study varies with concentration from 4-28 7 nm, see Table 7. This assumes that the density of asphaltene in the thin adsorbed film is similar to its 29 value in the bulk.…”
Section: Discussion 29mentioning
confidence: 94%
See 2 more Smart Citations
“…The average nanoaggregate molecular weight in solution with toluene appears to range between 2-12 monomers per aggregate (Yarranton et al, 2000;McKenna et al, 2013).The association increased with concentration reaching a limiting value at asphaltene concentrations of 10 -20 g/L. Barrera et al (2013) observed average molecular weights of the asphaltenes ranging from 1,000 to 30,000 g/mol, equivalent to approximately 1−30 molecules per nanoaggregate, using vapor pressure osmometry (VPO). However, SANS and SAXS data suggest much wider molecular weight distribution with average molecular weights in the order of 30,000 g/mol (Yarranton et al, 2013).…”
Section: Asphaltene Aggregationmentioning
confidence: 99%